2014
DOI: 10.1002/cctc.201402717
|View full text |Cite
|
Sign up to set email alerts
|

Methane Catalytic Combustion over Hierarchical Pd@CeO2/Si‐Al2O3: Effect of the Presence of Water

Abstract: The influence of water vapor on methane catalytic combustion was studied over a Pd@CeO2/Si‐Al2O3 catalyst, carefully designed to maximize Pd‐CeO2 interaction and prevent metal sintering and compared to a conventional impregnated catalyst with identical chemical composition. Although the nanostructured Pd@CeO2/Si‐Al2O3 catalyst is thermally stable, the addition of water to the reaction feed leads to a transient deactivation at low temperatures, consistent with the well documented competitive adsorption. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
59
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 49 publications
(81 reference statements)
3
59
2
Order By: Relevance
“…3. As reported previously [8,9], Pd@CeO 2 /Si-Al 2 O 3 catalysts calcined at 773 K deactivate rapidly in the WGS environment due to reduction of the ceria, which in turn causes a loss in the CO adsorption uptakes on Pd, probably due to the ceria shell closing up around the Pd [23]. This is shown in Fig.…”
Section: Wgs Activitymentioning
confidence: 56%
See 1 more Smart Citation
“…3. As reported previously [8,9], Pd@CeO 2 /Si-Al 2 O 3 catalysts calcined at 773 K deactivate rapidly in the WGS environment due to reduction of the ceria, which in turn causes a loss in the CO adsorption uptakes on Pd, probably due to the ceria shell closing up around the Pd [23]. This is shown in Fig.…”
Section: Wgs Activitymentioning
confidence: 56%
“…Reduction of the Pd@CeO 2 /Si-Al 2 O 3 occurred gradually with decreasing P(O 2 ). Since spectroscopic data showed that the Pd in these catalysts is easily oxidized to PdO [23], the results in Fig. 4B imply that the PdO and CeO 2 reduction occur together.…”
Section: Wgs Activitymentioning
confidence: 91%
“…Methane conversion over 5P5C-SCS increased with increasing operating temperature with full conversion attained at around 410 • C. It was worth noticing that under similar reaction conditions, complete combustion of methane over conventional 5P-I and 5P5C-I catalysts was never achieved. Secondly, contrary to the conventional 5P-I and 5P5C-I catalysts, the 5P5C-SCS nanocatalyst exhibited superior activity with no sign of deactivation in the temperature range betweeñ 400 and 800 • C. This behavior of the SCS catalysts resembled the core shell catalysts that have made a breakthrough in methane oxidation research [25,34]. On the other hand, the SCS catalysts were superior to the traditional catalysts which all showed significant deactivation at high temperature [15,19,20].…”
Section: Catalytic Activitymentioning
confidence: 88%
“…The adsorption of O 2 on oxygen vacancies, presumably followed by its dissociation is expected to play a major role in the oxidation reaction. It is generally accepted that the prevalent mechanism of the high temperature CH 4 catalytic oxidation involves a redox Mars-van Krevelen-type reaction [20,34,66]. In the present catalysts, the point of interaction between Pd and CeO 2 and/or the intrinsic oxygen vacancies presumably acted as centers for dissociating molecular oxygen into chemisorbed oxygen (O*) which were then consumed in the oxidation reaction.…”
Section: Catalytic Activitymentioning
confidence: 98%
See 1 more Smart Citation